SpringerOpen Newsletter

Receive periodic news and updates relating to SpringerOpen.

This article is part of the series Proceedings of the International Congress in Honour of Professor Hari M. Srivastava.

Open Access Research

Some circular summation formulas for theta functions

Yi Cai, Si Chen and Qiu-Ming Luo*

Author Affiliations

Department of Mathematics, Chongqing Normal University, Chongqing Higher Education Mega Center, Huxi Campus, Chongqing, 401331, People’s Republic of China

For all author emails, please log on.

Boundary Value Problems 2013, 2013:59  doi:10.1186/1687-2770-2013-59

The electronic version of this article is the complete one and can be found online at: http://www.boundaryvalueproblems.com/content/2013/1/59


Received:10 December 2012
Accepted:26 February 2013
Published:26 March 2013

© 2013 Cai et al.; licensee Springer

This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Abstract

In this paper, we obtain some circular summation formulas of theta functions using the theory of elliptic functions and show some interesting identities of theta functions and applications.

MSC: 11F27, 33E05, 11F20.

Keywords:
circular summation; elliptic functions; theta functions; theta function identities

1 Introduction

Throughout this paper we take q = e i π τ , where ( τ ) > 0 . The classical Jacobi theta functions θ i ( z | τ ) , i = 1 , 2 , 3 , 4 , are defined as follows:

(1.1)

(1.2)

(1.3)

(1.4)

Recently, Chan, Liu and Ng [1] proved Ramanujan’s circular summation formulas and derived identities similar to Ramanujan’s summation formula and connected these identities to Jacobi’s elliptic functions.

Subsequently, Zeng [2] gave a generalized circular summation of the theta function θ 3 ( z | τ ) as follows:

(1.5)

where

C 33 ( a , b ; y , τ ) = k n m 1 + + m a + n 1 + + n b = 0 m 1 , , m a , n 1 , , n b = q m 1 2 + + m a 2 + n 1 2 + + n b 2 e 2 k ( m 1 + + m a ) i y .

A special case of formula (1.5) yields the following result (see [[1], Theorem 3.1]):

s = 0 k n 1 θ 3 k ( z k n + π s k n | τ k n 2 ) = C 33 ( k , 0 ; 0 , τ k n 2 ) θ 3 ( z | τ ) , (1.6)

where

C 33 ( k , 0 ; 0 , τ ) = k n m 1 + + m k = 0 m 1 , , m k = q m 1 2 + + m k 2 . (1.7)

Upon a, b, n and k are any positive integer with k = a + b .

More recently, Liu further obtained the general formulas for theta functions (see [3]), but from one main result, Theorem 1 of Liu, we do not deduce our results in the present paper. Many people research the circular summation formulas of theta functions and find more interesting formulas (see, for details, [4-15]).

In the present paper, we obtain analogues and uniform formulas for theta functions θ 1 ( z | τ ) , a θ 2 ( z | τ ) , θ 3 ( z | τ ) and θ 4 ( z | τ ) . We now state our result as follows.

Theorem 1For any positive integerk, n, aandbwith k = a + b , α = 1 , 2 , β = 3 , 4 .

Fora, beven, we have

(1.8)

Foraeven, nandbodd, we have

(1.9)

(1.10)

where

C α β ( a , b ; y , τ ) = k n i a α q a 4 e a b i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) α ( m 1 + + m a ) + ( β + 1 ) ( n 1 + + n b ) × q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a e ( 2 k ( m 1 + + m a ) + a 2 ) i y . (1.11)

2 Proof of Theorem 1

From Jacobi’s theta functions (1.1)-(1.4), we have the following properties respectively:

(2.1)

(2.2)

(2.3)

(2.4)

From (2.1)-(2.4), by using the induction, we easily obtain

(2.5)

(2.6)

(2.7)

(2.8)

Let

f ( z ) = s = 0 k n 1 θ α a ( z k n + y a + π s k n | τ k n 2 ) θ β b ( z k n y b + π s k n | τ k n 2 ) . (2.9)

Case 1. When α = 1 , β = 3 .

The function f ( z ) becomes of the following form:

f ( z ) = s = 0 k n 1 θ 1 a ( z k n + y a + π s k n | τ k n 2 ) θ 3 b ( z k n y b + π s k n | τ k n 2 ) . (2.10)

From (2.10) we easily obtain

(2.11)

(2.12)

Comparing (2.11) and (2.12), when a is even, we get

f ( z + π ) = f ( z ) . (2.13)

By (2.5) and (2.7), and noting that a + b = k , we obtain

f ( z + π τ ) = s = 0 k n 1 θ 1 a ( z k n + y a + π s k n + n π τ k n 2 | τ k n 2 ) θ 3 b ( z k n y b + π s k n + n π τ k n 2 | τ k n 2 ) = ( 1 ) n a q 1 e 2 i z s = 0 k n 1 θ 1 a ( z k n + y a + π s k n | τ k n 2 ) θ 3 b ( z k n y b + π s k n | τ k n 2 ) . (2.14)

Obviously, when a is even, we have

f ( z + π τ ) = q 1 e 2 i z f ( z ) . (2.15)

We construct the function f ( z ) θ 3 ( z | τ ) . By (2.13) and (2.15), we find that the function f ( z ) θ 3 ( z | τ ) is an elliptic function with double periods π and πτ and only has a simple pole at z = π 2 + π τ 2 in the period parallelogram. Hence the function f ( z ) θ 3 ( z | τ ) is a constant, say, this constant is denoted by C 13 ( a , b ; y , τ ) , i.e.,

f ( z ) θ 3 ( z | τ ) = C 13 ( a , b ; y , τ ) ,

we have

f ( z ) = C 13 ( a , b ; y , τ ) θ 3 ( z | τ ) . (2.16)

By (1.3), (2.10) and (2.16), we have

(2.17)

By (1.1) and (1.3), we obtain

(2.18)

By equating the constant term of both sides of (2.18), we obtain

(2.19)

Clearly,

C 13 ( a , b ; y , τ ) = C 13 ( a , b ; y a b , τ k n 2 ) , (2.20)

where

(2.21)

In the same manner as in Case 1, we can obtain Case 2 below.

Case 2. When α = 2 , β = 3 .

The function f ( z ) becomes of the following form:

f ( z ) = s = 0 k n 1 θ 2 a ( z k n + y a + π s k n | τ k n 2 ) θ 3 b ( z k n y b + π s k n | τ k n 2 ) . (2.22)

From (2.22) we easily obtain

(2.23)

(2.24)

Comparing (2.23) and (2.24), when a is even, we get

f ( z + π ) = f ( z ) . (2.25)

By (2.6) and (2.7), and noting that a + b = k , we obtain

f ( z + π τ ) = s = 0 k n 1 θ 2 a ( z k n + y a + π s k n + n π τ k n 2 | τ k n 2 ) θ 3 b ( z k n y b + π s k n + n π τ k n 2 | τ k n 2 ) = q 1 e 2 i z s = 0 k n 1 θ 2 a ( z k n + y a + π s k n | τ k n 2 ) θ 3 b ( z k n y b + π s k n | τ k n 2 ) . (2.26)

Obviously, we have

f ( z + π τ ) = q 1 e 2 i z f ( z ) . (2.27)

We construct the function f ( z ) θ 3 ( z | τ ) . By (2.25) and (2.27), we find that the function f ( z ) θ 3 ( z | τ ) is an elliptic function with double periods π and πτ and only has a simple pole at z = π 2 + π τ 2 in the period parallelogram. Hence the function f ( z ) θ 3 ( z | τ ) is a constant, say, this constant is denoted by C 23 ( a , b ; y , τ ) , i.e.,

f ( z ) θ 3 ( z | τ ) = C 23 ( a , b ; y , τ ) ,

we have

f ( z ) = C 23 ( a , b ; y , τ ) θ 3 ( z | τ ) . (2.28)

By (1.3), (2.22) and (2.28), we have

(2.29)

By (1.2) and (1.3), we obtain

(2.30)

By equating the constant term of both sides of (2.30), we obtain

C 23 ( a , b ; y , τ ) = k n q a 4 k n 2 e i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a k n 2 × e 2 i y a b [ k ( m 1 + + m a ) + a 2 2 ] . (2.31)

Clearly,

C 23 ( a , b ; y , τ ) = C 23 ( a , b ; y a b , τ k n 2 ) , (2.32)

where

C 23 ( a , b ; y , τ ) = k n q a 4 e a b i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a × e ( 2 k ( m 1 + + m a ) + a 2 ) i y . (2.33)

Case 3. When α = 1 , β = 4 .

The function f ( z ) becomes of the following form:

f ( z ) = s = 0 k n 1 θ 1 a ( z k n + y a + π s k n | τ k n 2 ) θ 4 b ( z k n y b + π s k n | τ k n 2 ) . (2.34)

From (2.34) we easily obtain

(2.35)

(2.36)

Comparing (2.35) and (2.36), when a is even, we have

f ( z + π ) = f ( z ) . (2.37)

By (2.5) and (2.8), and noting that a + b = k , we obtain

f ( z + π τ ) = s = 0 k n 1 θ 1 a ( z k n + y a + π s k n + n π τ k n 2 | τ k n 2 ) θ 4 b ( z k n y b + π s k n + n π τ k n 2 | τ k n 2 ) = ( 1 ) k n q 1 e 2 i z s = 0 k n 1 θ 1 a ( z k n + y a + π s k n | τ k n 2 ) θ 4 b ( z k n y b + π s k n | τ k n 2 ) . (2.38)

• When a and b are even, then kn is also even, we have

f ( z + π τ ) = q 1 e 2 i z f ( z ) . (2.39)

We construct the function f ( z ) θ 3 ( z | τ ) , by (2.37) and (2.39), we find that the function f ( z ) θ 3 ( z | τ ) is an elliptic function with double periods π and πτ and only has a simple pole at z = π 2 + π τ 2 in the period parallelogram. Hence the function f ( z ) θ 3 ( z | τ ) is a constant, say, this constant is denoted by C 14 ( a , b ; y , τ ) , i.e.,

f ( z ) θ 3 ( z | τ ) = C 14 ( a , b ; y , τ ) ,

we have

f ( z ) = C 14 ( a , b ; y , τ ) θ 3 ( z | τ ) . (2.40)

By (1.3), (2.34) and (2.40), we have

(2.41)

By (1.1) and (1.4), we obtain

(2.42)

By equating the constant term of both sides of (2.42), we obtain

C 14 ( a , b ; y , τ ) = k n i a q a 4 k n 2 e i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) m 1 + + n b × q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a k n 2 e 2 i y a b [ k ( m 1 + + m a ) + a 2 2 ] . (2.43)

• When a is even, n and b are odd, then kn is also odd, we have

f ( z + π τ ) = q 1 e 2 i z f ( z ) . (2.44)

We construct the function f ( z ) θ 4 ( z | τ ) . By (2.37) and (2.44), we find that the function f ( z ) θ 4 ( z | τ ) is an elliptic function with double periods π and πτ and only has a simple pole at z = π 2 + π τ 2 in the period parallelogram. Hence the function f ( z ) θ 4 ( z | τ ) is a constant, say, this constant is denoted by C 14 ( a , b ; y , τ ) , i.e.,

f ( z ) θ 4 ( z | τ ) = C 14 ( a , b ; y , τ ) ,

we have

f ( z ) = C 14 ( a , b ; y , τ ) θ 4 ( z | τ ) . (2.45)

By (1.4), (2.34) and (2.45), we have

(2.46)

By (1.1) and (1.4), we obtain

(2.47)

By equating the constant term of both sides of (2.47), we obtain

C 14 ( a , b ; y , τ ) = k n i a q a 4 k n 2 e i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) m 1 + + n b × q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a k n 2 e 2 i y a b [ k ( m 1 + + m a ) + a 2 2 ] . (2.48)

Clearly, in (2.43) and (2.48), we have

C 14 ( a , b ; y , τ ) = C 14 ( a , b ; y a b , τ k n 2 ) ,

where

C 14 ( a , b ; y , τ ) = k n i a q a 4 e a b i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) m 1 + + n b × q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a e ( 2 k ( m 1 + + m a ) + a 2 ) i y . (2.49)

In the same manner as in Case 3, we can obtain Case 4 below.

Case 4. When α = 2 , β = 4 .

The function f ( z ) becomes of the following form:

f ( z ) = s = 0 k n 1 θ 2 a ( z k n + y a + π s k n | τ k n 2 ) θ 4 b ( z k n y b + π s k n | τ k n 2 ) . (2.50)

• When a and b are even, we have

(2.51)

(2.52)

• When a is even, n and b are odd, we have

f ( z ) = C 24 ( a , b ; y , τ ) θ 4 ( z | τ ) , (2.53)

C 24 ( a , b ; y , τ ) = k n q a 4 k n 2 e i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) n 1 + + n b × q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a k n 2 e 2 i y a b [ k ( m 1 + + m a ) + a 2 2 ] . (2.54)

Clearly, in (2.52) and (2.54), we have

C 24 ( a , b ; y , τ ) = C 24 ( a , b ; y a b , τ k n 2 ) ,

where

C 24 ( a , b ; y , τ ) = k n q a 4 e a b i y m 1 , , m a , n 1 , , n b = 2 ( m 1 + + m a + n 1 + + n b ) + a = 0 ( 1 ) n 1 + + n b q m 1 2 + + m a 2 + n 1 2 + + n b 2 + m 1 + + m a × e ( 2 k ( m 1 + + m a ) + a 2 ) i y . (2.55)

Therefore we complete the proof of Theorem 1.

3 Some special cases of Theorem 1

In this section we give some special cases of Theorem 1 and obtain some interesting identities of theta functions.

Corollary 1For any positive integern, we have

(3.1)

(3.2)

(3.3)

(3.4)

where C 13 ( 2 , 2 ; y , τ ) and C 24 ( 2 , 2 ; y , τ ) are defined by (2.21) and (2.55), respectively.

Proof Taking a = b = 2 and α = 1 , β = 3 in (1.11), we have

(3.5)

Taking a = b = 2 and α = 2 , β = 4 in (1.11), we have

C 24 ( 2 , 2 ; y , τ ) = 4 n q 1 2 m 1 , m 2 , n 1 , n 2 = m 1 + m 2 + n 1 + n 2 + 1 = 0 ( 1 ) n 1 + n 2 q m 1 2 + m 2 2 + n 1 2 + n 2 2 + m 1 + m 2 e 8 i y ( m 1 + m 2 ) e 5 i y = 4 n e 3 i y θ 1 2 ( 4 y | τ ) θ 3 2 ( 0 | τ ) . (3.6)

Obviously, we find that C 13 ( 2 , 2 ; y , τ ) = C 24 ( 2 , 2 ; y , τ ) = 4 n e 3 i y θ 1 2 ( 4 y | τ ) θ 3 2 ( 0 | τ ) . □

Taking n = 1 and letting z 4 z , y 2 y , τ 4 τ in Corollary 1, we get the following identities for theta functions:

(3.7)

(3.8)

(3.9)

Further, taking y = 0 in the above identities, we obtain the following additive formulas of the theta function θ 3 ( z | τ ) :

θ 3 ( 4 z | 4 τ ) = 1 4 θ 1 2 θ 3 2 [ θ 1 2 ( z | τ ) θ 3 2 ( z | τ ) + θ 1 2 ( z + π 4 | τ ) θ 3 2 ( z + π 4 | τ ) + θ 1 2 ( z + π 2 | τ ) θ 3 2 ( z + π 2 | τ ) + θ 1 2 ( z + 3 π 4 | τ ) θ 3 2 ( z + 3 π 4 | τ ) ] (3.10)

= 1 4 θ 1 2 θ 3 2 [ θ 2 2 ( z | τ ) θ 4 2 ( z | τ ) + θ 2 2 ( z + π 4 | τ ) θ 4 2 ( z + π 4 | τ ) + θ 2 2 ( z + π 2 | τ ) θ 4 2 ( z + π 2 | τ ) + θ 2 2 ( z + 3 π 4 | τ ) θ 4 2 ( z + 3 π 4 | τ ) ] , (3.11)

where θ 1 = θ 1 ( 0 | τ ) , θ 3 = θ 3 ( 0 | τ ) .

Similarly, we have the following.

Corollary 2For any positive integern, we have

(3.12)

(3.13)

(3.14)

(3.15)

where C 14 ( 2 , 2 ; y , τ ) = C 23 ( 2 , 2 ; y , τ ) = 4 n e 3 i y θ 2 2 ( 4 y | τ ) θ 3 2 ( 0 | τ ) are defined by (2.49) and (2.33), respectively.

Taking n = 1 and letting z 4 z , y 2 y , τ 4 τ in Corollary 2, we get the following identities of theta functions:

(3.16)

(3.17)

(3.18)

Further, taking y = 0 in the above identities, we obtain other additive formulas for the theta function θ 3 ( z | τ ) as follows:

θ 3 ( 4 z | 4 τ ) = 1 4 θ 2 2 θ 3 2 [ θ 1 2 ( z | τ ) θ 4 2 ( z | τ ) + θ 1 2 ( z + π 4 | τ ) θ 4 2 ( z + π 4 | τ ) + θ 1 2 ( z + π 2 | τ ) θ 4 2 ( z + π 2 | τ ) + θ 1 2 ( z + 3 π 4 | τ ) θ 4 2 ( z + 3 π 4 | τ ) ] (3.19)

= 1 4 θ 2 2 θ 3 2 [ θ 2 2 ( z | τ ) θ 3 2 ( z | τ ) + θ 2 2 ( z + π 4 | τ ) θ 3 2 ( z + π 4 | τ ) + θ 2 2 ( z + π 2 | τ ) θ 3 2 ( z + π 2 | τ ) + θ 2 2 ( z + 3 π 4 | τ ) θ 3 2 ( z + 3 π 4 | τ ) ] , (3.20)

where θ 2 = θ 2 ( 0 | τ ) , θ 3 = θ 3 ( 0 | τ ) .

Taking a = 2 , b = 1 in (1.9), (1.10) and (1.11), we have the following.

Corollary 3Fornodd, we have

(3.21)

(3.22)

(3.23)

(3.24)

where C 14 ( 2 , 2 ; y , τ ) and C 24 ( 2 , 2 ; y , τ ) are defined by (2.49) and (2.55), respectively.

Proof Taking a = 2 , b = 1 and α = ( 1 , 2 ) , β = 4 in (1.11), we have

(3.25)

(3.26)

 □

Taking n = 1 and letting z 3 z , y 2 y , τ 3 τ in Corollary 3, we get the following identities for theta functions:

(3.27)

and

(3.28)

Further taking y = 0 in the above identities, we obtain the following additive formulas for the theta function θ 4 ( z | τ ) as follows:

θ 4 ( 3 z | 3 τ ) = 1 3 θ 3 θ 2 2 [ θ 1 2 ( z | τ ) θ 4 ( z | τ ) + θ 1 2 ( z + π 3 | τ ) θ 4 ( z + π 3 | τ ) + θ 1 2 ( z + 2 π 3 | τ ) θ 4 ( z + 2 π 3 | τ ) ] (3.29)

and

θ 4 ( 3 z | 3 τ ) = 1 3 θ 3 θ 1 2 [ θ 2 2 ( z | τ ) θ 4 ( z | τ ) + θ 2 2 ( z + π 3 | τ ) θ 4 ( z + π 3 | τ ) + θ 2 2 ( z + 2 π 3 | τ ) θ 4 ( z + 2 π 3 | τ ) ] , (3.30)

where θ 1 = θ 1 ( 0 | τ ) , θ 2 = θ 2 ( 0 | τ ) , θ 3 = θ 3 ( 0 | τ ) .

Corollary 4Whennis odd, we have

s = 0 k n 1 ( 1 ) s θ 2 k ( z + π s k n | τ ) = C 33 ( k , 0 ; 0 , τ ) θ 2 ( k n z | k n 2 τ ) , (3.31)

where C 33 ( k , 0 ; 0 , τ ) is defined by (1.7).

Proof Replacing z by k n z + k n π + k n 2 π τ 2 and τ by k n 2 τ in (1.6), we obtain

(3.32)

Substituting n by 2 n + 1 in the left-hand side of (3.32), we get (3.31). □

Competing interests

The authors declare that they have no competing interests.

Authors’ contributions

All authors contributed equally in writing this paper, and read and approved the final manuscript and.

Acknowledgements

Dedicated to Professor Hari M Srivastava.

The present investigation was supported, in part, by Research Project of Science and Technology of Chongqing Education Commission, China under Grant KJ120625, Fund of Chongqing Normal University, China under Grant 10XLR017 and 2011XLZ07 and National Natural Science Foundation of China under Grant 11226281 and 11271057.

References

  1. Chan, HH, Liu, ZG, Ng, ST: Circular summation of theta functions in Ramanujan’s lost notebook. J. Math. Anal. Appl.. 316, 628–641 (2006). Publisher Full Text OpenURL

  2. Zeng, XF: A generalized circular summation of theta function and its application. J. Math. Anal. Appl.. 356, 698–703 (2009). Publisher Full Text OpenURL

  3. Liu, ZG: Some inverse relations and theta function identities. Int. J. Number Theory. 8, 1977–2002 (2012). Publisher Full Text OpenURL

  4. Berndt, BC: Ramanujan’s Notebooks, Part III, Springer, New York (1991).

  5. Berndt, BC: Ramanujan’s Notebooks, Part V, Springer, New York (1998).

  6. Chan, SH, Liu, ZG: On a new circular summation of theta functions. J. Number Theory. 130, 1190–1196 (2010). Publisher Full Text OpenURL

  7. Chua, KS: The root lattice A n and Ramanujan’s circular summation of theta functions. Proc. Am. Math. Soc.. 130, 1–8 (2002). Publisher Full Text OpenURL

  8. Chua, KS: Circular summation of the 13th powers of Ramanujan’s theta function. Ramanujan J.. 5, 353–354 (2001). Publisher Full Text OpenURL

  9. Liu, ZG: A theta function identity and its implications. Trans. Am. Math. Soc.. 357, 825–835 (2005). Publisher Full Text OpenURL

  10. Ono, K: On the circular summation of the eleventh powers of Ramanujan’s theta function. J. Number Theory. 76, 62–65 (1999). Publisher Full Text OpenURL

  11. Ramanujan, S: The Lost Notebook and Other Unpublished Papers, Narosa, New Delhi (1988)

  12. Shen, LC: On the additive formula of the theta functions and a collection of Lambert series pertaining to the modular equations of degree 5. Trans. Am. Math. Soc.. 345, 323–345 (1994)

  13. Son, SH: Circular summation of theta functions in Ramanujan’s lost notebook. Ramanujan J.. 8, 235–272 (2004)

  14. Zhu, JM: An alternate circular summation formula of theta functions and its applications. Appl. Anal. Discrete Math.. 6, 114–125 (2012). Publisher Full Text OpenURL

  15. Zhu, JM: A note on a generalized circular summation formula of theta functions. J. Number Theory. 132, 1164–1169 (2012). Publisher Full Text OpenURL